SPIA's approach to impact assessment for CGIAR - CGIAR Standing Panel on Impact Assessment (CGIAR Advisory Services, 2020)
The CGIAR portfolio spans a wide spectrum of research, development, and policy engagement activities, involving a multitude of disciplines and approaches, and a large set of causal pathways, and possible outcomes. The commonality across this wide portfolio is that CGIAR aims to provide public goods, which potentially benefit many populations in different parts of the world. It is the global public good nature of CGIAR activities that provides the theoretical rationale for support of the system. Yet evidence for the large-scale impact of more recent investments in CGIAR is scarcer and maintaining confidence in the system requires an updated approach to impact evidence. SPIA’s mandate—providing evidence on the impacts at the system level of a set of agricultural research-for-development (AR4D) centers and programs that are themselves portfolios of research and development programs and projects—is possibly unique in international development. This challenge is complex and distinct from the evaluation of an individual research or development intervention.